Pengaruh Motivasi, Komunikasi dan Budaya Organisasi terhadap Kinerja Karyawan - Eni Erwantiningsih (University of Merdeka Malang, 2019)
The purpose of this research is to analyze the influence of motivation, communication and organizational culture to employee performance. The object of this study is Merdeka University Pasuruan. Data collected through questionnaires given to 42 respondents of educational staff taken by census method. The results show that: 1) motivatian has a significant effect on employee performance, 2) communication does not have a significant effect on employee performanc,e 3) organizational culture has a significant effect on employee performance, and 4) organizational culture has a dominant effect on employee performance.https://doi.org/10.26905/jmdk.v7i2.3247